Diseño y Validación de Antenas Flexibles en la Banda de 4G/LTE para Sistemas de Radio Comunicación Móvil con Geometría Esférica - Coto-Salazar, Rolando (Instituto Tecnológico de Costa Rica, 2018)
The present work shows the process of study, design, and implementation of multi-band exible antennas for 4G/LTE applications. These antennas must be able to adjust physically to the dimensions of spheric geometry and operate in the cellular telephone bands of service operators in the United States. Antenna simulation models are analyzed based on microwave parameters on at surfaces and under deformation in the vicinity of the device. The tests of physical antennas are carried out in terms of return loss measurements (jS11j) to validate the methodology and the simulations results. Two designs are nally proposed, which are successfully implemented, based on triangle shape antennas and cavity PIFA.
Proyecto de Graduación (Licenciatura en Ingeniería Electrónica) Instituto Tecnológico de Costa Rica, Escuela de Ingeniería Electrónica, 2018.
Keywords: Antenas; Bounce Explorer; Simulación; Research Subject Categories::TECHNOLOGY::Electrical engineering, electronics and photonics::Electronics; Superficies